Proses Pengembangan Hubungan Bagi Masyarakat Yang Bertempat Tinggal Di Huntap Buddha Tzu Chi Tondo Kota Palu - Khair, Zaidul (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the process of developing relationships for people who live in permanent housing (HUNTAP) Buddha Tzu Chi Tondo Palu City, the theory used in this study is the theory of social penetration. This study uses a research method with a case study approach through data collection techniques using in-depth interviews, observations, then the data is processed and analyzed using, data reduction, data presentation, and drawing conclusions. The number of informants in this study was five (5) people, namely, people who live in permanent housing (HUNTAP) Buddha Tzu Chi Tondo Palu City who were selected through purposive sampling techniques. The results of the study show that in the process of developing relationships from the beginning until now living in permanent housing (HUNTAP) Buddha Tzu Chi Tondo Palu City is going well, which is indicated by the efforts made to establish relationships such as greeting, giving smiles, and trying to interact with fellow residents of permanent housing. The topics of discussion ranged from general to specific, such as discussions included information about names, addresses, ethnicities, blogs, and the natural disaster of September 28, 2022. They also included specific or personal discussions, such as sharing their feelings, giving each other input, things they liked and disliked, and humor.